Florida Medicinal Garden Plants: Skullcap (Scutellaria spp.) - Amanda Morgan; Brian J. Pearson (EDIS, 2018)
Scutellaria species (spp.) are perennial, herbaceous plants that are cultivated for both their ornamental and medicinal value. This 5-page document describes the uses and growing requirements of this species. Written by Amanda Morgan and Brian Pearson and published by the UF/IFAS Environmental Horticulture Department, September 2018. http://edis.ifas.ufl.edu/ep564